Hungarian Monitoring, 12 October 1989 . [Magyar rádiófigyelő], 1989. október 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Dialog between Party and people in the GDR - USA: Senate and administration want to offer much less support than expected to Eastern European countries Domestic Affairs: - Franz Vranitzky and Miklós Németh in discussions in Sopron - Opposition between Pozsgay and Nyers factions almost causes split at Hungarian Socialist Party (MSZP) founding congress - Alliance of Young Democrats (Fidesz) press conference - Second national Calvinist revival conference - The Tőkés affair - André Erdős's speech at the UN Economy: - EEC Committee recommends that majority of import restrictions on Polish and Hungarian goods be suspended Külpolitika: - Párbeszéd a párt és a nép között az NDK-ban - USA: a tervezettnél jóval kevesebb támogatást kíván nyújtani a Szenátus és kormány a Kelet-európai országoknak Belpolitika: - Franz Vranitzky és Németh Miklós tárgyalása Sopronban - Az MSZP alakuló kongresszusán csaknem szakadáshoz vezetett a Pozsgay-Nyers frakció közötti szembenállás - Fidesz sajtótájékoztató - 2. országos református megújulási konferencia - Tőkés-ügy - Erdős André felszólalása az ENSZ-ben Gazdaság: - Az E.G.K. Bizottsága javasolta, hogy függesszék fel a lengyel és a magyar árucikkeket sújtó importkorlátozások többségét